Nadmierna zależność małżonka od rodziny generacyjnej jako źródło niezdolności w podjęciu istotnych obowiązków małżeńskich - Cynkier, Przemysław; Majchrzyk, Zdzisław (Ius Matrimoniale, 2013)
This paper aims at discussing possible conditioning of the future bridegroom’s overdependence on his generational family. Theories analyzing family life identify few possible variants of how such dependence may occur. According to systems theory, the young man’s separation from the family is due not so much to his personal features but the whole dynamic structure of the family. Sometimes to retain homeostasis (maintain family structure), the family strives to keep the future bridegroom within the family. Family loyalty theory elaborates such a hypothesis. Attachment theories reach even deeper into the structures of human psyche, assuming that the model of adult interpersonal relations –that should be fully realized in marriage – depends on the patterns of childhood contacts with one’s parents or legal guardians. If the future bridegroom depends too much on his parents, he may find it difficult to fulfill his marital obligations. The paper proposes to focus on the family structure of the future bridegroom before the marriage is solemnized. Just then, with the help of the church and therapeutic institutions, such family can be diagnosed and actions undertaken toward autonomy and independence of the future spouse, while maintaining satisfactory relations with his generational family.